2002
DOI: 10.1177/03635465020300050801
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of a Preseason Exercise Program to Prevent Adductor Muscle Strains in Professional Ice Hockey Players

Abstract: A therapeutic intervention of strengthening the adductor muscle group appears to be an effective method for preventing adductor strains in professional ice hockey players.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
136
0
9

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(149 citation statements)
references
References 16 publications
1
136
0
9
Order By: Relevance
“…6,31,52 Weakness and poor endurance of the lumbar extensor, gluteus maximus, and hip external rotator muscles have also been noted in individuals with lower extremity injuries and low back pain. 9,28,31,32,36,39 Leetun et al 31 found that athletes who were not injured had stronger hip abductor and external rotator muscles.…”
Section: Discussionmentioning
confidence: 99%
“…6,31,52 Weakness and poor endurance of the lumbar extensor, gluteus maximus, and hip external rotator muscles have also been noted in individuals with lower extremity injuries and low back pain. 9,28,31,32,36,39 Leetun et al 31 found that athletes who were not injured had stronger hip abductor and external rotator muscles.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, overlapping diagnoses can also skew the exact incidence. Groin strains are among the most common injuries seen in ice hockey players [13][14][15]. It has been documented that groin strains accounted for 10 % of all injuries in elite Swedish ice hockey players [16].…”
Section: Adductor Muscle Strainsmentioning
confidence: 99%
“…Now that the researchers can identify players at risk for a future adductor strain, the next step is to design an intervention program to address all risk factors. Tyler et al [13] were able to demonstrate that a therapeutic intervention of strengthening the adductor muscle group could be an effective method for preventing adductor strains in professional ice hockey players. Prior to the 2000 and 2001 seasons, professional ice hockey players were tested for strength.…”
Section: Adductor Muscle Strainsmentioning
confidence: 99%
“…A ratio of 95% adductor to abductor strength was shown in injured National Hockey League (NHL) players compared with a ratio of 78% in injured players [43]. A prevention programme consisting of a warm up, adductor strengthening and sports specific training, with a minimum goal of 80% adductor to abductor strength, reduced the incidence of adductor strains from 8% to 2% compared with the previous 2 seasons [43]. The Adductor Muscle Strain injury prevention programme is shown in Table 4.…”
Section: Adductor Painmentioning
confidence: 99%